141k views
2 votes
Steven is solving the equation 3(8−2x)+40=34. He begins with the following two steps.

Step 1: 3(8)+3(−2x)+40=34

Step 2: 24−6x+40=34

Which of the following is the best next step for Steven to take in solving the equation?

Question 4 options:

Multiply both sides by –6.


Add 24 and 40.


Add 24 to both sides.


Add 24 and 34.

2 Answers

4 votes

Answer:

Add 24 and 40

Explanation:

3(8 - 2x) + 40 = 34 use the distributive property a(b + c) = ab+ ac

3(8) + 3(-2x) + 40 = 34

24 - 6x + 40 = 34 combine like terms

-6x + (24 + 40) = 34 Answer: Add 24 and 40

-6x + 64 = 34 subtract 64 from both sides

-6x = -30 divide both sides by (-6)

x = 5

User Ogzd
by
4.9k points
2 votes

Answer:

Add 24 and 40.

Explanation:

Steven is solving the equation
3(8-2x)+40=34

Step 1:


3(8)+3(-2x)+40=34

Step 2:


24-6x+40=34

So, according to pemdas, the next step is Add 24 and 40.

Then this becomes:

Step 3:


64-6x=34

So, the answer will be option 2: Add 24 and 40.

User Jordon Willis
by
5.0k points